Professional Pluralism in an Industrial Organization - Ritti, R. R.; Goldner, Fred H. (Management Science, 1969)
Large, technologically-based industrial organizations are composed of many-specialist functions whose interests are frequently seen to be in conflict with those of management. Conflict within such organizations occurs over mutually dependent claims to shares of limited resources necessary to further specialist aims and programs. To understand the management process—the allocation of these resources—that takes place in such organizations the following points are crucial: (1) The technology-based organization generally has many “managements” that pursue goals relevant to their specialties (e.g. engineering or manufacturing). (2) Conflict occurs among managements over specialist interests that have often been described as professional interests. (3) Where specialties have become bureaucratized, where projects have a complex division of labor over both individuals and time, specialist interests will be protected not by professionals or the “profession” but rather by someone with formal executive authority who is responsible for a work force of specialists. For not only is the work force one of both managers and specialists, but their tasks are group tasks. Survey and interview data from one large technologically-based company illustrate the existence of horizontally contending factions rather than the customarily envisioned management-specialist schism. Specialists become managers and executives in order to perform “professional” functions.